The Influence of Different Caregivers on Infant Growth and Development in China - Li, Qinrui; Liang, Furong; Liang, Weilan; Zhang, Jing; Niu, Manman; Han, Ying (Frontiers in Pediatrics, 2017)
Objective An increasing number of parents in China ask grandparents or babysitters to care for their children. Modern parents are often the only child in their family because of China’s One-Child Policy and thus may lack interaction with siblings. Accordingly, the present study aimed to explore whether different caregivers affect the physical and development of infants in China. Methods In total, 2514 infants were enrolled in our study. We assessed their weight-for-age, supine length-for-age, weight-for-length, occipital-frontal circumference (OFC), and Denver Developmental Screening Test (DDST) results and recorded their general parental information and their primary caregivers. Results The weights and lengths of 12-month-old infants under the care of babysitters were significantly lower than those of infants under the care of parents or grandparents (P<0.05). Additionally, 12-month-old infants under the care of babysitters had the lowest DDST pass rate (75%) among the three groups (χ2=11.819, P=0.012), especially for the fine motor-adaptive and language domains. Compared to 12-month-old infants under the care of parents and babysitters, infants under the care of grandparents were more likely to be overweight or obese (P<0.001). Conclusions The study showed that caregivers had a dominant role in the physical and cognitive development of the infants. Specifically, compared with infants raised by grandparents and parents, 12-month-old infants under the care of babysitters had partially suppressed lengths and weights and lagged cognitively. The 12-month-old infants under the care of grandparents were more overweight than those cared for by parents and babysitters. by parents and babysitters.